The Effectiveness of the Environmental Health Services in the Primary Health Care Against the Prevention of Pulmonary Tuberculosis in the Regency of Banyuwangi - Rachman Setiawan; Endang Sri Lestari; Jojok Mukono; Endro Sukmono (JURNAL KESEHATAN LINGKUNGAN, 2020)
Introduction: One of the promotive and preventive efforts in the prevention of pulmonary tuberculosis (TB) disease in primary health care is a health services environment that includes counseling, inspection and intervention of environmental health. The purpose of this study is to evaluate the effectiveness of the Environmental health services in the primary health care against the prevention of Pulmonary TB disease in Regency of Banyuwangi. Method: This research was observational descriptive design of study cross-ssectional. The study population was the primary health care in districy of Banyuwangi and a large sample of 6 primary health care. The determination of the study sample by using purposive sampling based on criteria of results Assessment of Performance of primary health care (PKP) services and programs environmental health in primary health cares and numbers Case Notification Rate (CNR) at the top of the East Java Province. Processing and analysis of data using a scoring system based on the scale of the theoretically grouped in the category of good, enough, less. The data is then interpreted descriptively. Result and Discussion: The Program of health service in the prevention of the disease is said to be effective when the probability of >50.00%. The results showed the probability of the effectiveness of the environmental health services in the Primary Health Care of Klatak of 77.00%. The Primary Health Care of Mojopanggung, Sobo, and Kabat respectively 78.80%, Primary Health Care of Gitik by 64.20% and the Primary Health Care of Songgon 49.50%. Human resources at the Primary Health Care of Songgon not competent. The Primary Health Care of Gitik and Songgon not planning activities. The achievement of the output in all the primary health care less, it is because of the lack of commitment of the implementers and the coordination of cross-program not running. Conclusion: There are 5 primary health cares service programs environmental health in the prevention of Pulmonary TB effective that the Primary Health Care of Klatak, Mojopangung, Sobo, Kabat and Gitik while at the Primary Health Care of Songgon is not effective. The effectiveness of services and programs environmental health in TB patients is influenced by policies, human resources, infrastructure, planning and coordination across the program.